On the treatment of Diabetus mellitus by acid extract of Duodenal Mucous Membrane - Benjamin Moore; E. S. Edie; John Hill Abram (1906)
The carrying out in the Bio-Chemical Laboratory of the experiments otn the secretion of organic acids in diabetes described in the previous paper supplied an opportuniity for testing the hypothesis that the internal secretion of the pancreas might be stimulated and initiated (similarly to the externial secretion) by a substance of the nature of a hormone or secretin yielded by the duodenal mucous membrane ; and that in certain cases of diabetes the appearance of sugar in the urine might be due to funictional disturbance occasioned by the absence of such an intestinial excitanit of the initernal secretion.The fact that an internal secretion of the pancreas is niecessary for the regulation of carbohydrate metabolism, and that in the absence of this secretion oxidation of dextrose canniot be carried out, with the result that death occurs from acute diabetes, has been clearly proven by the experimenits of Minkowski and v. Mering,; and others on complete and partial panicreas removal, and the history of the subject is too well-known to require detailed description here.It was suggested by Schafer that the formation of the internal pancreatic secretion might possibly bc due to peculiar nests of cells of different form and staining properties to the other secreting cells of the gland.These cells from their isolated appearanice, and after the name of the observer who first described them, are called the 'islets of Langerhans.'